Brief Report: Malignancies in Adults Living With HIV in Asia. (1st March 2019) - Jiamsakul, Awachana; Polizzotto, Mark; Wen-Wei Ku, Stephane; Tanuma, Junko; Hui, Eugenie; Chaiwarith, Romanee; Kiertiburanakul, Sasisopin; Avihingasanon, Anchalee; Yunihastuti, Evy; Kumarasamy, Nagalingeswaran; Ly, Penh Sun; Pujari, Sanjay; et al.
Abstract : Background: Hematological malignancies have continued to be highly prevalent among people living with HIV (PLHIV). This study assessed the occurrence of, risk factors for, and outcomes of hematological and nonhematological malignancies in PLHIV in Asia. Methods: Incidence of malignancy after cohort enrollment was evaluated. Factors associated with development of hematological and nonhematological malignancy were analyzed using competing risk regression and survival time using Kaplan–Meier. Results: Of 7455 patients, 107 patients (1%) developed a malignancy: 34 (0.5%) hematological [0.08 per 100 person-years (/100PY)] and 73 (1%) nonhematological (0.17/100PY). Of the hematological malignancies, non-Hodgkin lymphoma was predominant (n = 26, 76%): immunoblastic (n = 6, 18%), Burkitt (n = 5, 15%), diffuse large B-cell (n = 5, 15%), and unspecified (n = 10, 30%). Others include central nervous system lymphoma (n = 7, 21%) and myelodysplastic syndrome (n = 1, 3%). Nonhematological malignancies were mostly Kaposi sarcoma (n = 12, 16%) and cervical cancer (n = 10, 14%). Risk factors for hematological malignancy included age >50 vs. ⩽30 years [subhazard ratio (SHR) = 6.48, 95% confidence interval (CI): 1.79 to 23.43] and being from a high-income vs. a lower-middle-income country (SHR = 3.97, 95% CI: 1.45 to 10.84). Risk was reduced with CD4 351–500 cells/µL (SHR = 0.20, 95% CI: 0.05 to 0.74) and CD4 >500 cells/µL (SHR = 0.14, 95% CI: 0.04 to 0.78), compared to CD4 ⩽200 cells/µL. Similar risk factors were seen for nonhematological malignancy, with prior AIDS diagnosis showing a weak association. Patients diagnosed with a hematological malignancy had shorter survival time compared to patients diagnosed with a nonhematological malignancy. Conclusions: Nonhematological malignancies were common but non-Hodgkin lymphoma was more predominant in our cohort. PLHIV from high-income countries were more likely to be diagnosed, indicating a potential underdiagnosis of cancer in low-income settings. Abstract : Supplemental Digital Content is Available in the Text.